2017
DOI: 10.3748/wjg.v23.i33.6065
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of NSAID-induced gastropathy as a “Translatable” model of referred visceral sensitivity

Abstract: AIMTo evaluate whether non-steroidal anti-inflammatory drugs (NSAIDs)-induced gastropathy is a clinically predictive model of referred visceral hypersensitivity.METHODSGastric ulcer pain was induced by the oral administration of indomethacin to male, CD1 mice (n = 10/group) and then assessed by measuring referred abdominal hypersensitivity to tactile application. A diverse range of pharmacological mechanisms contributing to the pain were subsequently investigated. These mechanisms included: transient receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(73 reference statements)
0
2
0
1
Order By: Relevance
“…Однако имеются данные, полученные в других ульцерогенных моделях, косвенно подтверждающие это предположение. Показано, что образование геморрагических эрозий СОЖ, индуцированных ульцерогенным действием индометацина, является источником Соматическая болевая чувствительность... висцеральной боли, что подтверждается ее «отражением» в абдоминальную область у мышей (увеличением чувствительности данной области к тактильным раздражителям) (Hummel et al 2017). Патологический процесс в желудке, индуцированный йодоацетоамидом, включающий, в том числе, и образование геморрагических эрозий, вызывает увеличение амплитуды висцеромоторного ответа на действие как механического (растяжение стенки желудка), так и химического стимула (интрагастральное введение кислоты), что является признаком висцеральной гиперчувствительности (гипералгезии) (Lamb et al 2003).…”
Section: Discussionunclassified
“…Однако имеются данные, полученные в других ульцерогенных моделях, косвенно подтверждающие это предположение. Показано, что образование геморрагических эрозий СОЖ, индуцированных ульцерогенным действием индометацина, является источником Соматическая болевая чувствительность... висцеральной боли, что подтверждается ее «отражением» в абдоминальную область у мышей (увеличением чувствительности данной области к тактильным раздражителям) (Hummel et al 2017). Патологический процесс в желудке, индуцированный йодоацетоамидом, включающий, в том числе, и образование геморрагических эрозий, вызывает увеличение амплитуды висцеромоторного ответа на действие как механического (растяжение стенки желудка), так и химического стимула (интрагастральное введение кислоты), что является признаком висцеральной гиперчувствительности (гипералгезии) (Lamb et al 2003).…”
Section: Discussionunclassified
“…It is possible that tissue acidosis, an important side effect of acetazolamide, be responsible for the higher frequency of diffuse abdominal pain and referred shoulder pain in group A in the recovery room. Bala et al (2015) observed that visceral pain scores were significantly lower while resting, coughing, and moving at 2, 4, 6, 12, and 4 hours postoperatively (16). The effect of a single dose of acetazolamide is known to last for 4-6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…AMG 9810 (2E)-N-(2,3-Dihydro-1,4-benzodioxin-6-yl)-3-[4-(1,1-dimethylethyl)phenyl]-2-propenamide (Enzo Life Sciences, Inc. NY, USA) and AMTB [N-(3-aminopropyl)-2-{[(3-methylphenyl) methyl]oxy}-N-(2-thienylmethyl)benzamide hydrochloride salt] (Wako Pure Chemical Industries Ltd. Osaka, Japan) were used as TRPV1 and TRPM8 antagonists, respectively. Various in vitro and in vivo studies showed the effeicacy of AMG 9810 and AMTB to block TRPV1 and TRPM8, respectively [71,72,73,74,75,76]. AMG 9810 was dissolved in small amount of DMSO and Tween 80 and diluted in normal saline.…”
Section: Methodsmentioning
confidence: 99%